Preservação digital na gestão da informação: um modelo processual para as instituições de ensino superior - Grácio, José Carlos Abbud [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Society has witnessed a cultural change in the use of information due to new technologies, mainly to computers and Internet. In this context, preservation of digital information emerges as a great challenge to be faced by information professionals, mainly derived from the constant enhancements and changes in information and communication technology (ICT), and in the environments in which information is inserted. Along with this new challenge, a new research area has been initiated, that of digital preservation whose agenda includes problems such as obsolescence of technological equipment (hardware), of computer programs (software), of information supports and of storage formats. Besides technological problems, digital preservation involves cultural, legal and managerial aspects. Although the concerns of the Information Area on the theme have been increasing, there is a need in literature to offer a sound theoretical discussion on issues related to it, and this is the proposal which may turn this research relevant. From the infinite universe of digital preservation applicability, the environment chosen for this research was that of Higher Education Institutions (HEI), where there has been an explosion of documents in digital form produced by teaching-learning activities in graduation and post graduation programs, research projects and community services. The aim of this investigation is to propose a processual management model for digital information preservation in HEI, by means of sound theoretical research on all the aspects involved in the preservation process and on the main information management models. The model should account for any type of HEI, any type of digital document, any type of academic information, and organizational culture should guide all processes. To achieve this goal, the exploratory methodology is adopted in order to be able to obtain a full understanding... (Complete abstract click electronic access below)

A sociedade atual tem presenciado uma mudança de cultura na utilização das informações, advinda principalmente da invenção dos computadores e do surgimento da Internet. Nesse contexto, surge um grande desafio a ser enfrentado, que é a preservação das informações digitais, principalmente em função das ininterruptas mudanças e avanços das tecnologias de informação e comunicação (TIC) e do ambiente no qual essas informações estão inseridas, e, com ele, uma nova área de pesquisa, a preservação digital, com sua pauta própria de problemas, como a obsolescência tecnológica dos equipamentos (hardware), dos programas de computador (software), dos suportes e dos formatos de armazenamento. Além dos problemas técnicos, a preservação digital envolve também aspectos culturais, legais e administrativos. Apesar de as discussões sobre a preservação digital serem uma preocupação crescente no contexto atual, esta pesquisa justifica-se por se observar, na literatura, a necessidade de um aprofundamento das questões relativas ao tema, uma vez que existem ainda poucas iniciativas nacionais e uma carência de modelos de gestão para preservação digital que abordem todos os aspectos a ela relacionados. Como a aplicabilidade da preservação digital é extensa, adotaram-se as instituições de ensino superior (IES) como universo desta pesquisa, devido à explosão documentária em meio digital que tem sido observada nessas instituições, em razão principalmente do grande crescimento das atividades de ensino, pesquisa e extensão. Nesse sentido, esta pesquisa tem como objetivo propor um modelo processual de gestão para preservação da informação digital em uma IES, por meio de um aprofundamento dos estudos sobre todos os aspectos envolvidos na preservação digital e dos principais modelos de gestão da informação, que atenda e possa ser adequado a qualquer tipo de IES...
Keywords: Documentos eletrônicos; Gerenciamento da informação; Tecnologia da informação; Universidades e faculdades; Cultura organizacional; Tecnologias de informação e comunicação; Digital Preservation; Higher Education Institutions; Organizational Culture; Information and Communication Technologies